The benefit of practical field experience (PPL) in improving the experience of teaching practice at school - Mega Silvia Sitompul; Carolina Carolina; Herman Herman; Rolan Manurung; Tutiariani Nasution (Abdimas Paspama, 2024)
The purpose of this article is the implementation of a field experience program (PPL) to provide practical teaching experience to prospective teachers in schools. This PPL activity begins with carrying out observations in accordance with the regulations set by the campus. After observation, students started heading to the school where the PPL was being held. The school where PPL is located is YP HKBP 1 Pematangsiantar Private High School. This PPL activity will be carried out from early October 2023 to the end of January 2024. This PPL activity aims not only to provide students with experience in teaching at school, but they are also given the task of carrying out school administration which is part of the work of a teacher at school. The result of this PPL activity is that the implementation of the PPL activity went well. Students can receive knowledge and experience from school that is not obtained at lectures, while schools gain new knowledge and knowledge with students as parties who are seen as continually updating information and knowledge. Suggestions that can be given to schools are that creativity and innovation carried out by teachers in learning are very necessary to create effective and enjoyable teaching and learning conditions.